Critical thinking: an experiment in initial teacher education - Fernandes, Fátima (2022)
It is undeniable that educational institutions play an important role in any society’s development. It is expected for schools to contribute to people’s development in a whole, as well as to prepare students for the personal, professional, social, and economic challenges that a constant changing world demands. Such form of education involves building knowledge, developing dispositions, values, abilities, and skills, so that individuals can have a holistic understanding of the world, while also knowing when and how to act in all life’s challenging situations. Being aware of how to think and act critically from early on is particularly decisive in initial teacher education curricula, especially in the Curricular Unit “Initiation to Professional Practice 3”, which was attended by 3rd year students of Basic Education of a Polytechnic Institute in the North of Portugal, in the 2020/2021 academic year. This was achieved throughout appropriate strategies and methodologies, which were able to promote: (1) the development of the students’ critical skills, who will ultimately become future education professionals; (2) the development of the students’ sensitivity to understand the decisive role they have in shaping their potential students’ future; and (3) their empowerment as promoters of critical thinking. It was the first time that students and teachers worked in this Curricular Unit and, therefore, from a methodological point of view, it was openly and experimental endeavour. Based on the resources and guidelines made available, and after carrying out various training actions with children ranging between three and 10 years old, in this experiment, future teachers were suggested to identify different educational contexts and practices and were proposed to carry out an analysis, an evaluation and a reflection of and on several parameter Based on the resources and guidelines made available, and after carrying out various training actions with children ranging between the ages of three and 10, in this experiment, future teachers were suggested to identify different educational contexts and practices while also being advised to carry out an analysis, an evaluation and a reflection of and on several parameters Data were mainly collected from written records made by students and from conversations between them and/or between students and teachers. All of these took place in the classroom, where all tasks were monitored. By analysing the collected data, it was made clear that the cognitive processes were highlighted during the resolution of the aforementioned tasks. That said, a few higher-level tasks were performed with certain difficulty by the students. They have reacted positively to these tasks, even though they have often focused on the content of the work instead of focusing on the skills as expected. Students have valued the opportunity to get to know different contexts, as well as various educational resources and model practices that could be applied in their future careers. By recognizing the importance of training selective, assertive, and thoughtful professionals, the teaching team believes that the Curricular Internship Units allow students to reflect critically about several aspects that relate, either directly or indirectly, to education, as well as to the sharing of exemplary, inspiring, challenging, innovative, and context-appropriate educational practices, experiments and resources.